2014
DOI: 10.1007/s11999-013-3068-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Total Knee Arthroplasty With Highly Congruent Anterior-stabilized Bearings versus a Cruciate-retaining Design

Abstract: Background The use of a highly conforming, anteriorstabilized bearing has been associated with clinical success in a limited number of studies. Questions/purposes We compared Knee Society scores, radiographic results, complication rates, and revision rates with the use of anterior-stabilized bearings compared with cruciate-retaining (CR) bearings. Methods A series of 382 patients with 468 primary total knee arthroplasties (TKAs) between 2003 and 2008 with minimum 2-year followup were reviewed. Anterior-stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 19 publications
4
54
1
1
Order By: Relevance
“…Even though a statistically significant difference in ROM between PS and CR groups was detected, both the underreporting of results and the difference in follow-up times may influence our results. For example, there were differences in the definition of postoperative, most reporting at 2 years 5,8,19,23,28,30,32,33,36,38,40,42,43,45 and some at 5 years. 2,3,9,14,17 Also, it is difficult to know at what time assessment was undertaken postoperatively for those who did not clarify their methods of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though a statistically significant difference in ROM between PS and CR groups was detected, both the underreporting of results and the difference in follow-up times may influence our results. For example, there were differences in the definition of postoperative, most reporting at 2 years 5,8,19,23,28,30,32,33,36,38,40,42,43,45 and some at 5 years. 2,3,9,14,17 Also, it is difficult to know at what time assessment was undertaken postoperatively for those who did not clarify their methods of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Complications were reported in only 17 of the 37 studies (45.9%). 3,[5][6][7]14,19,20,22,28,30,32,33,[35][36][37]44,45 There was an overall complication rate of 3.9% (213 complications in 5,407 knees). The meta-analysis 3,6,20,22,29,35,45 showed that no statistical difference was found between the two procedures (95% CI, 0.78-2.31; p ¼ 0.29).…”
Section: Range Of Motion and Complicationsmentioning
confidence: 99%
“…The remainder was performed with anterior-stabilizing or more constrained designs. Indications for performing a more constrained design were based on the integrity of the posterior cruciate ligament (PCL), severe deformity, or ligamentous deficiencies as we have previously described [19]. Only the CR TKAs were used as the control group in an effort to minimize confounding variables.…”
Section: Methodsmentioning
confidence: 99%
“…The precise role of the posterior cruciate ligament (PCL) in CR TKA is unclear; however, most researchers believe that retaining the PCL greatly increases dynamic knee stability and retains femoral rollback during flexion and extension of the knee. Unlike with posterior stabilized TKA, the difficulty associated with performing CR TKA is how to achieve optimal PCL strain when balancing knee flexion and extension.…”
Section: Introductionmentioning
confidence: 99%